Complex Fluid-Flows in Microfluidics - Galindo-Rosales, Francisco José (Springer International Publishing : Imprint: Springer, 2018)
This monograph contains expert knowledge on complex fluid-flows in microfluidic devices. The topical spectrum includes, but is not limited to, aspects such as the analysis, experimental characterization, numerical simulations and numerical optimization. The target audience primarily comprises researchers who intend to embark on activities in microfluidics. The book can also be beneficial as supplementary reading in graduate courses. .